Children’s Inter-Individual Variability and Asthma Development - Saadeh, Rami; Klaunig, James (International Journal of Health Sciences, 2015)
Children of different ages vary in their response to environmental stressors due to their continuous development and changes in their bodies’ anatomy, physiology, and biochemistry. Each age group in children has special biological features that distinguish their toxicokinetic and toxicodynamic characteristics from other age groups. The variability in responses extends to include children of the same age group. These intra- and inter- group differences in the biological features account to the variability in responses to similar environmental exposures. Based on such differences in children’s responses to exposures, adverse health outcomes and diseases develop differently in children. One of these diseases that are common in children is asthma. Asthma is a complex respiratory chronic disease that is multifactorial in origin. This paper discusses how variability in certain factors among children contributes to asthma occurrence or exacerbation, and links these factors to asthma in children of different ages. The importance of this review is to provide an insight on factors affecting asthma prevalence among children. These factors are usually overlooked in clinical or public health practice, which might significantly affect asthma management, and decrease the predictability of asthma detection measures. Therefore, the keeping these factors into consideration can significantly improve asthma treatment and assist in asthma prevention amongst susceptible populations.